2019
DOI: 10.1080/19420862.2019.1661736
|View full text |Cite
|
Sign up to set email alerts
|

DuoMab: a novel CrossMab-based IgG-derived antibody format for enhanced antibody-dependent cell-mediated cytotoxicity

Abstract: High specificity accompanied with the ability to recruit immune cells has made recombinant therapeutic antibodies an integral part of drug development. Here we present a generic approach to generate two novel IgG-derived antibody formats that are based on a modification of the CrossMab technology. MoAbs harbor two heavy chains (HCs) resulting in one binding entity and one fragment crystallizable region (Fc), whereas DuoMabs are composed of four HCs harboring two binding entities and two Fc regions linked at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…32,33 While our work was under review for publication, a complete characterization of DuoMAbs was published. 34 Structurally, the DuoMAbs may be more planar than tetrahedral, which may also be the case for our dual Fc. It In the future, the in vitro and in vivo activity of this 2Fc mAb could be assessed to determine whether the observed increase in binding avidity has functional consequences at physiological densities of FcR.…”
Section: Discussionmentioning
confidence: 69%
“…32,33 While our work was under review for publication, a complete characterization of DuoMAbs was published. 34 Structurally, the DuoMAbs may be more planar than tetrahedral, which may also be the case for our dual Fc. It In the future, the in vitro and in vivo activity of this 2Fc mAb could be assessed to determine whether the observed increase in binding avidity has functional consequences at physiological densities of FcR.…”
Section: Discussionmentioning
confidence: 69%
“…All proteins described in this study were produced via secretion into culture supernatants in the same manner as regular IgGs and bsAbs which has been previously described 14 . Expression plasmids that contain CMV-promoter driven expression cassettes for secretion of H- or L- and/or dummy-chains were transiently co-transfected in suspension HEK cells, applying either cells and matching transfection reagents of the human embryonic kidney 293-F cells using the FreeStyle ™ 293 system according to the manufacturer’s instruction (ThermoFisher/Invitrogen) for individual larger scale purifications.…”
Section: Methodsmentioning
confidence: 99%
“…Bi- or multivalency of targeting arms can for example induce intracellular pathways, including tumor-targeted activation of death receptor mediated apoptosis 13 . Vice versa, modification or multiplication of constant regions can modulate or enhance Fc-mediated functionalities 14 . Other examples that highlight the functional importance of the geometry and arrangement of binders include the necessity to combine compatible epitopes and geometries to achieve functional linking of clotting factors 15 , 16 , and observations that blood–brain–barrier-penetration functionalities of bispecific antibodies depend on affinity and valency of their shuttle modules 17 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to affinity modulation, avidity modulation is a less established but more straightforward approach. Fc duplication (or tandem-Fc) or multiplication, whereby multiple Fcs are linked within one IgG1 molecule, has been shown to augment FcγR binding avidity and increase ADCC and ADCP [ 56 , 57 , 58 , 59 ] ( Figure 2 C). A theoretical safety concern for Fc multiplication strategies is the fact that natural antibody oligomerization may result in unwanted immune activation [ 60 ].…”
Section: Fc Engineering To Enhance Fc-effector Functionsmentioning
confidence: 99%
“…A theoretical safety concern for Fc multiplication strategies is the fact that natural antibody oligomerization may result in unwanted immune activation [ 60 ]. However, studies have reported minimal in vitro aggregation and no in vivo adverse events so far [ 57 , 59 ].…”
Section: Fc Engineering To Enhance Fc-effector Functionsmentioning
confidence: 99%